Information and Trust in Parent-Teacher Cooperation - Connections with Educational Inequality - Markus P. Neuenschwander (Debrecen University Press, 2020)
There is an ongoing debate on how parents and the cooperation between parents and teachers contribute to educational inequality. In this study, the assumption that information and trust in parent-teacher cooperation mediate the effects of parent socioeconomic status (SES) on student achievement in mathematics and instruction language (German) was examined. The effects of information and trust on achievement were assumed to be mediated by parent self-efficacy expectation in German. The hypotheses were tested using a sample with 1001 students from 4th to 6th grade and their parents in Swiss primary schools using questionnaires and achievement tests at the beginning and the end of a school year. Results from structural equation models with longitudinal data showed that parent trust and parent self-efficacy expectation fully mediated the effect of SES and student achievement in language instruction but not in mathematics. Information did not correlate with SES nor with student achievement, but with trust. Parental trust in the cooperation with teachers affected achievement in both mathematics and German. The model combines the research on parental involvement with the research on educational inequality in school. Teachers need to establish trust in cooperation with low-SES parents to reduce educational inequality in school.